Water mites (Acari: Hydrachnidia) from interstitial waters of Iran, with the description of one new species - Pesic, Vladimir; Saboori, Alireza; Asadi, Mahdieh; Vafaei, Reza (Zootaxa, 2005)
New records of water mites (Acari: Hydrachnidia) from interstitial waters of Iran are presented. Fourteen species are recorded, of which six are new for the studied area. Kongsbergia persica sp. nov. is described; the zoogeographical and ecological significance of these new records is discussed.